2016
DOI: 10.2118/179550-pa
|View full text |Cite
|
Sign up to set email alerts
|

Determining Diffusion Coefficients for Carbon Dioxide Injection in Oil-Saturated Chalk by Use of a Constant-Volume-Diffusion Method

Abstract: Summary This paper presents a novel technique to determine multicomponent diffusion coefficients for carbon dioxide (CO2) injection in a North Sea chalk field (NSCF) in Norway at reservoir conditions. The constant-volume-diffusion (CVD) method is used, consisting of an oil-saturated-chalk core in contact with an overlying free space, which is filled with the CO2. The experimental data are matched with an equation-of-state (EOS) -based compositional model. Transport by diffusion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The direct upscaling strategy would be beneficial since the laboratory cores are subjected to a greater contact surface and a longer treatment period for the injected gas than may be the case in the field. Ghasemi et al 105 suggested a technique of constant volume diffusion for the CO 2 injection displacement process in the Chalk Field, North Sea. The tests performed with this methodology not only confirmed the significance of the diffusion process, but it also demonstrated that the reciprocal diffusion between gas and oil could reduce the convection influence initiated by the concentration variation.…”
Section: Gas-eor Mechanism In Shale/tightmentioning
confidence: 99%
“…The direct upscaling strategy would be beneficial since the laboratory cores are subjected to a greater contact surface and a longer treatment period for the injected gas than may be the case in the field. Ghasemi et al 105 suggested a technique of constant volume diffusion for the CO 2 injection displacement process in the Chalk Field, North Sea. The tests performed with this methodology not only confirmed the significance of the diffusion process, but it also demonstrated that the reciprocal diffusion between gas and oil could reduce the convection influence initiated by the concentration variation.…”
Section: Gas-eor Mechanism In Shale/tightmentioning
confidence: 99%
“…Therefore, a full understanding of the behavior of CO 2 under reservoir conditions has always been one of the main interests of researchers and the petroleum industry. There are several processes involved in the CO 2 EOR, i.e., diffusion of CO 2 into the crude oil in the porous rocks [9][10][11][12][13][14][15][16][17][18][19], the chemical reaction of CO 2 with formation minerals [20,21], and rock mechanics caused by pore pressure changes [22]. Only the first process of CO 2 diffusion in porous media is considered in this study, which has theoretical importance and meaning for applications in the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research by Ghasemi et al, the average diffusivity of ethane and butane in the gas phase of stagnant tank oil and live oil is approximately 6 × 10 –5 and 6 × 10 –4 m 2 /day, respectively . Li et al and Jia et al reported that the diffusivity of CO 2 in porous media is on the order of 10 –5 m 2 /day. , Using these literature data as a reference, we tested the distance that the most mobile HCG would travel with diffusivity values of 5 × 10 –4 and 5 × 10 –3 m 2 /day.…”
Section: Resultsmentioning
confidence: 99%